Komunikasi Segerak Berkesan Sebagai Strategi Untuk Meningkatkan Prestasi Organisasi Dalam Sektor Awam - SHAFI, MUHAMMAD AMMAR; Ramasamy, Chandrashekar; Yusoff, Mohd Zarir; Zulkipli, Hafizah (Research in Management of Technology and Business, 2023)
Synchronous communication can be defined as communication between two individuals simultaneously through face-to-face interaction, mobile phones, electronic devices, and this type of communication can lead to issues related to intra-communication convenience, such as infrequent use of intranets and ineffective utilization of primary communication channels. The objective of this study is to identify the relationship between the effectiveness of synchronous communication and organizational performance, and quantitative methods such as questionnaires were employed to conduct this study. A set of questionnaire items and necessary materials were provided to respondents for the study. Secondary sources like journals, articles, newspapers, books, websites were utilized to gather data, which was subsequently analyzed using the Statistical Package for Social Science (SPSS) application. Key findings and trends from the data suggest that synchronous communication has a significant impact among employees within the organization, serving as a channel for information and resources flow. A relationship exists between effective synchronous communication and employee performance. Thus, all employees take steps to enhance their communication skills to be conscious of communication's effects on performance. Employees need to overcome communication barriers to improve employee productivity and organizational performance. In light of this study, the researcher recommends that employees should use simple and clear language, emphasize clarity, and avoid using ambiguous terms. Active listening, such as attentive and thorough listening, is also recommended.